Small Island Avifauna Diversity at Sebatik Island of Sabah, Malaysia - Wing-Shen Lim; Andy Russel Mojiol (2020)
Preliminary study was commenced to investigate the avifauna diversity presented on Sebatik Island in Sabah. Opportunistic sampling was conducted at four villages and along Sungai Haji Kuning for three days. A total of 28 avifauna individuals belonged to 13 different species were observed on Sebatik Island, which were mainly comprised of carnivorous and non-threatened resident species. All recorded migratory avifauna species, as well as the five avifauna species sighted along Sungai Haji Kuning, were determined as carnivores, hence indicating the relationship between migratory behaviour and habitat type with feeding guild of local avifauna. Since that there were no significant differences in avifauna species composition and abundance, thus both human settlement and riverine mangrove habitats were vital to the survival of both migratory and resident species. Because of that, conservation effort is required to preserve this small island habitat and its avifauna inhabitants from being threatened by anthropogenic disturbances.